First synthesis of nitrosporeusines, alkaloids with multiple biological activities - Philkhana, Satish Chandra; Jachak, Gorakhnath R.; Gunjal, Vidya B.; Dhage, Nagsen M.; Bansode, Ajay H.; Reddy, D. Srinivasa (Tetrahedron Letters, 2015)
Synthesis of nitrosporeusines A and B, thioester-bearing alkaloids from the Arctic Streptomyces nitrosporeus with exceptional biological activity is disclosed for the first time. In addition, we have prepared another biologically important natural product, maleimycin, in optically pure form using a gram-scale enzymatic resolution method. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Enzymatic resolution; Influenza H1N1 virus; Maleimycin; Michael reaction; Nitrosporeusine

AgNO3-Catalysed intramolecular cyclization: access to functionalized cyclopentanones and spiro-cyclopentanones - Bhoite, Shubhangi P.; Bansode, Ajay H.; Burate, Pralhad A.; Suryayanshi, Gurunath (Asian Journal of Organic Chemistry, 2019)
An efficient AgNO3-catalysed method has been developed for the synthesis of functionalized cyclopentanones and spiro-cyclopentanones through intramolecular cyclization between ynones and cyanoacrylate/aryl/alkylidene malononitrile using DBU as a base. Easy availability of starting materials and mild reaction conditions makes this protocol more feasible over previously reported methods. The functionalized cyclopentanones and spiro-cyclopentanones were synthesized in good to excellent yields with a broad substrate scope.

Iodine-mediated oxidative rearrangement of alpha,beta-unsaturated diaryl ketones: a facile access to 1,2-diaryl diketones - Bansode, Ajay H.; Suryavanshi, Gurunath (ACS Omega, 2019)
A metal-free oxidative rearrangement was explored for the synthesis of 1,2-diaryl diketones by utilizing alpha, beta-unsaturated diaryl ketones and I-2/TBHP in good to high yields. The reaction proceeds via oxidative aryl migration, followed by C-C bond cleavage. A simple and high-yielding protocol was developed for the synthesis of a wide range of 1,2-diaryl diketones, which are the backbone for a variety of medicinally important molecules.

Hypervalent iodine(iii) induced oxidative olefination of benzylamines using Wittig reagents - Ramavath, Vijayalakshmi; Rupanawar, Bapurao D.; More, Satish G.; Bansode, Ajay H.; Suryavanshi, Gurunath (New Journal of Chemistry, 2021)
We have developed hypervalent iodine(iii) induced oxidative olefination of primary and secondary benzylamines using 2C-Wittig reagents, which provides easy access to alpha,beta-unsaturated esters. Mild reaction conditions, good to excellent yields with high (E) selectivity, and a broad substrate scope are the key features of this reaction. We have successfully carried out the gram-scale synthesis of alpha,beta-unsaturated esters.

Visible-light-induced controlled oxidation of N-substituted 1,2,3,4-tetrahydroisoquinolines for the synthesis of 3,4-dihydroisoquinolin-1(2h)-ones and isoquinolin-1(2H)-ones - Bansode, Ajay H.; Suryavanshi, Gurunath (Advanced Synthesis & Catalysis, 2021)
A visible light-rose bengal-TBHP mediated, controlled oxidation of N-substituted 1,2,3,4-tetrahydroisoquinolines is developed for the synthesis of 3,4-dihydroisoquinolin-1(2H)-ones and isoquinolin-1(2H)-ones. The present method feature's a broad substrate scope, good functional group tolerances, and the products were prepared in good to excellent yields. The developed methodology further demonstrated in the synthesis of isoindolo[2,1-b] isoquinolin-5(7H)-one (topoisomerase-I inhibitor).
Keywords: 2; 3; 4-Dihydroisoquinolin-1(2H)-one; 4-tetrahydroisoquinolines; Isoquinolin-1(2H)-one; N-substituted 1; Oxidation; Photocatalysis

Hypervalent-iodine-mediated base-free oxidative olefination of benzylic amines to access α,β-unsaturated ketones - Rupanawar, Bapurao D.; Bansode, Ajay H.; Suryavanshi, Gurunath (Synlett, 2025)
We report a one-pot base-free protocol for the oxidative olefination of benzylic amines promoted by a hypervalent iodine reagent for the synthesis of alpha,beta-unsaturated ketones. Mechanistically, (diacetoxyiodo)benzene oxidizes the benzylic amine to the corresponding imine, which, on reaction with a phenacyl(triphenyl)phosphonium bromide salt and an in situ generated acetoxy anion leads to an alpha,beta-unsaturated ketone. A wide range of alpha,beta-unsaturated ketones were easily accessed through direct oxidative olefination of substituted benzylic amines in good to excellent yields and with high E -selectivity.
Keywords: benzylic amines; enones; hypervalent iodine; olefination; Oxidation